Protein‐Polymer Bioconjugates Prepared by Post‐Polymerization Modification of Alternating Copolymers. Issue 21 (23rd August 2021) - Saxer, Samantha; Erdogan, Omer; Paniagua, Cédric; Chavanieu, Alain; Garric, Xavier; Darcos, Vincent
Abstract: Protein‐polymer bioconjugates have shown great promise in biomedical and life science applications including drug delivery and diagnosis. The current bioconjugation strategies suffer from lack of efficiency and versatility. In this article, poly(styrene‐ alt ‐maleic anhydride) copolymers were first prepared by RAFT polymerization and characterized by different analytical techniques. Then, the poly(styrene‐ alt ‐maleic anhydride) precursors were functionalized with primary amine such as azidopropylamine and amino poly(ethylene glycol). The reaction of amino compounds with maleic anhydride was found to be a highly efficient, a versatile, and a facile chemical ligation reaction for the synthesis of macromolecules with quantitative yield under mild conditions. The main benefit is the incorporation of a wide range of functionality by easily changing the primary amine compound. For the amphiphilic graft copolymers based on poly(ethylene glycol), aggregation behavior in water was investigated. In a second part, azido‐functionalized polystyrene copolymers were used to prepare a new protein‐polymer bioconjugate by copper‐free click chemistry reaction. Abstract : A straightforward strategy is proposed for the synthesis of protein‐polymer bioconjugates using one of the oldest polymers, the poly(styrene‐ alt ‐maleic anhydride). Different poly(styrene‐ alt ‐maleic anhydride) copolymers were successfully prepared by RAFT polymerization in dioxane using the 2‐cyano‐2‐propyl dodecyl trithiocarbonate as chain transfer agent (CTA) and AIBN as initiator. Original biomacromolecules were successfully prepared by post‐polymerization modification.